Expression of transforming growth factor-β after different non-invasive facial rejuvenation modalities - El-Domyati, Moetaz; El-Ammawi, Tarek S.; Medhat, Walid; Moawad, Osama; Mahoney, Mỹ G.; Uitto, Jouni (International journal of dermatology, 2015)
Background Transforming growth factor‐β (TGF‐β) is a major regulator of the synthesis of extracellular matrix (ECM) proteins in human skin as it stimulates fibroblast proliferation and collagen production. Perturbed TGF‐β expression may play a key role in the pathogenesis of skin aging. Objectives This study was conducted to objectively evaluate the effects of different modalities of non‐invasive facial rejuvenation on TGF‐β expression and to correlate its level with that of newly synthesized collagen. Methods A total of 36 patients with Fitzpatrick skin types III and IV were divided into six groups. Each group of six patients was subjected to a different non‐invasive modality for the treatment of skin aging, including radiofrequency (RF), Nd:YAG 1320‐nm laser and Er:YAG 2940‐nm laser mini‐peels, intense pulsed light (IPL), mesotherapy injection, and electro‐optical synergy (ELOS). Skin biopsies were obtained before treatment, at the end of treatment, and at three months post‐treatment. In addition, biopsies were obtained from 30 control subjects. Levels of TGF‐β were quantitatively evaluated using computerized image analysis of immunostained sections. Results The expression of TGF‐β was statistically significantly increased (P < 0.05) at the end of Nd:YAG 1320‐nm and Er:YAG 2940‐nm mini‐peel treatments compared with baseline levels, and at three months post‐treatment with RF and ELOS compared with pretreatment and end‐of‐treatment levels. However, no significant differences (P > 0.05) were observed in TGF‐β level in response to IPL or mesotherapy treatments in comparison with baseline. The level of TGF‐β was positively correlated (P < 0.05) to that of newly synthesized collagen at the end of Nd:YAG 1320‐nm laser and Er:YAG 2940‐nm laser mini‐peels, as well as at three months after RF and ELOS treatments. Conclusions Radiofrequency, ELOS, and Nd:YAG 1320‐nm laser and Er:YAG 2940‐nm laser mini‐peels resulted in an increase in TGF‐β expression, which may mediate the effects of these modalities in enhancing dermal collagen expression through the activation of fibroblasts and thereby reverse the photoaging of skin.